Climate services needs in Mekong River Delta: flood irrigation paddy - Barlis, Angelica; Vu Huong, Ngan; Nguyen, Nhiem Duy; Swaans, Cornelis P.M. (2022)
This info brief presents the key findings from the climate risk workshop (CRW) in Vietnam specifically from the Mekong River Delta region. CRW is part of the climate service demand assessment by determining the climate and risk impact on main agricultural livelihoods, mapping the current and available farm management practices that farmers and local networks carry out to cope with climate variability to identify opportunities for improved practices using climate information and agro-advisory services.